Development of Nanoformulation for Injectable Delivery of Sertraline: Enhancing Efficacy and Patient Compliance in Depression Treatment - Zainab Noori Salman; Noor Mustafa Shaker (International Journal of Medical Toxicology and Legal Medicine, 2024)
Injectable long-acting dosage forms are a highly preferred option in numerous treatment modalities, such as cancer, diabetes, and bacterial infections. This approach can produce better patient compliance and minimize the problems related to improved therapeutic efficacy, toxicity, affordability, and bioavailability. Depression is the most prevalent psychological disorder, and it is considered to be the second leading cause of disabilities. However, breakthrough innovations are desperately needed in contemporary medication due to increasingly painful and embarrassing dosing regimens. When patients adhere to their drug dosage, health benefits are enhanced. Nonetheless, depressive patients are more likely to experience treatment failure. If the rate of compliance could be increased, the benefits of depression treatment could also be improved. Conventional pharmacological dosage forms of sertraline face challenges such as poor solubility, limited ability in target localization, and dose-dependent adverse reactions. Researchers are currently fascinated by the prospective applications of nanotechnology in this field. Nanotechnology, particularly for drug delivery applications, could resolve many obstacles. Nanoparticles are particularly attractive carriers for use with injectable antidepressants to effectively deliver them to the brain. This manuscript illustrates that a suitable nanoformulation strategy for the injectable distribution of sertraline, one of the leading antidepressants, can significantly increase effective use and subsequently patient compliance.